Studi Literatur tentang Peran Transformasi Digital Bank Syariah dalam Meningkatkan Inklusi Keuangan di Indonesia - Rona Wiransya Repormantika; Yudha Budi Abadi; Wiwik Wimbawani (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
This study aims to analyze the role of digital transformation in Islamic banks in enhancing financial inclusion in Indonesia. Using a literature study method, the research examines previous studies, official reports from the Financial Services Authority (OJK) and Bank Indonesia (BI), as well as academic publications related to the digitalization of Islamic banking. The findings reveal that digital transformation, through services such as mobile banking, internet banking, QRIS, and integration with Islamic fintech, significantly contributes to expanding access to financial services, particularly for the unbanked and underbanked groups. The growth of assets, third-party funds (DPK), and the number of accounts in 2024 indicate the rising level of Islamic financial inclusion. Furthermore, digital product innovations such as insurtech and wealthtech enhance the competitiveness of Islamic banks, while digital literacy programs initiated by regulators improve public acceptance of technology-based services. Regulatory support through the Financial Sector Development and Strengthening Law (PPSK), OJK regulations, and the Islamic finance industry roadmap has further strengthened the foundation of digitalization. However, challenges such as low digital financial literacy, limited infrastructure, and cybersecurity risks remain to be addressed. Overall, digital transformation not only broadens Islamic financial inclusion but also supports the empowerment of MSMEs, creates competitive advantages, and promotes sustainable economic growth based on Islamic values.